Phytohormonal modulation of the drought stress in soybean: outlook, research progress, and cross-talk - Shaffique, Shifa; Hussain, Saddam; Kang, Sang-Mo; Imran, Muhamad; Injamum-Ul-Hoque, Md.; Khan, Muhammad Aaqil; Lee, In-Jung (Frontiers in Plant Science, 2023)
Phytohormones play vital roles in stress modulation and enhancing the growth of plants. They interact with one another to produce programmed signaling responses by regulating gene expression. Environmental stress, including drought stress, hampers food and energy security. Drought is abiotic stress that negatively affects the productivity of the crops. Abscisic acid (ABA) acts as a prime controller during an acute transient response that leads to stomatal closure. Under long-term stress conditions, ABA interacts with other hormones, such as jasmonic acid (JA), gibberellins (GAs), salicylic acid (SA), and brassinosteroids (BRs), to promote stomatal closure by regulating genetic expression. Regarding antagonistic approaches, cytokinins (CK) and auxins (IAA) regulate stomatal opening. Exogenous application of phytohormone enhances drought stress tolerance in soybean. Thus, phytohormone-producing microbes have received considerable attention from researchers owing to their ability to enhance drought-stress tolerance and regulate biological processes in plants. The present study was conducted to summarize the role of phytohormones (exogenous and endogenous) and their corresponding microbes in drought stress tolerance in model plant soybean. A total of n=137 relevant studies were collected and reviewed using different research databases.